Teacher’s classroom management practices for increasing effectiveness in climate change in Nigeria. - Badau, K. M. (Advances in Social Sciences Research Journal, 2016)
Classroom environment and cultures as well as the ways in which both students and learning are organized and managed increase teachers’ effectiveness in climate change. The effective teacher manages the large number of relatively diverse students who occupy these classrooms within the environment. The importance of physical environment, climate culture, organization and management of classroom within the larger context of teachers effectiveness is mostly clearly seen by noting that beginning or novice teachers takes longer time to be effective in the classroom. This paper discuss classroom management practices for teacher effectiveness in terms of environment climate culture, organization and management in a climate change. Conclusion and recommendations on managing classroom for increasing teacher effectiveness in climate change for policy makers and educational planners in Nigeria were offered.